Evaluation of cavitation erosion resistance of Al-Si casting alloys: effect of eutectic and intermetallic phases (Fracture and Structural Integrity, 2017)
In the present paper, the influence of eutectic and intermetallic phases on cavitation resistance of Al-Si alloys was studied. In fact, Al-Si alloys are commonly used for the production of components, such as cylinders, pistons, pumps, valves and combustion chambers, which in service may incur in cavitation phenomenon. Samples of AlSi3, AlSi9 and AlSi9CuFe were characterized from the microstructural point of view. Hardness measurements were also performed. Subsequently, cavitation tests were carried out according to ASTM G32 standard and the erosion mechanism was examined by scanning electron microscope. It was found the both eutectic and intermetallic phases enhance cavitation resistance, expressed in terms of mass loss. Particularly, intermetallic particles with complex morphologies provide a positive contribution, exceeding that of other microstructural features, as grain size. The effect of T6 heat treatment was also evaluated. It was confirmed that the precipitation of fine strengthening particles in the Al matrix successfully hinders the movement of dislocations, resulting in a longer incubation stage and a lower mass loss for heat-treated samples in comparison with as-cast ones. Finally, the relationship between cavitation resistance and material hardness was investigated.
Keywords: Cavitation erosion; Scanning Electron Microscopy; Al-Si alloys; Brinell hardness; Intermetallics